2013
DOI: 10.1016/j.tet.2012.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis studies on the Melodinus alkaloid meloscine

Abstract: The pentacyclic Melodinus alkaloid (±)-meloscine was synthesized in 19 chemical steps from 2-bromobenzaldehyde through a route featuring an allenyl azide cyclization cascade to deliver the core azabicyclo[3.3.0]octane substructure. Peripheral functionalization of this core included a Tollens-type aldol condensation to set the quaternary center at C(20) and a diastereoselective ring closing metathesis to forge the tetrahydropyridine ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Manipulations to form the metathesis precursor 8 for the formation of ring D began with the chemoselective reduction of malonate 9 to the corresponding diol under optimised conditions (LiAlH 4 , room temperature, 15 min; Scheme ). A concise route to 8 , based on work by Feldman and Antoline, was to oxidise the diol to a dialdehyde, followed by a Wittig reaction to give dialkene 8 . However, degradation was observed during the oxidation, and no appropriate conditions could be found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulations to form the metathesis precursor 8 for the formation of ring D began with the chemoselective reduction of malonate 9 to the corresponding diol under optimised conditions (LiAlH 4 , room temperature, 15 min; Scheme ). A concise route to 8 , based on work by Feldman and Antoline, was to oxidise the diol to a dialdehyde, followed by a Wittig reaction to give dialkene 8 . However, degradation was observed during the oxidation, and no appropriate conditions could be found.…”
Section: Resultsmentioning
confidence: 99%
“…Retrosynthetically, access to both targets 1 and 6 would involve the formation of ring D by diastereoselective ring‐closing metathesis of 8 to give a common intermediate 7 (Scheme ). The two C20 vinyl substituents would be derived from malonate 9 .…”
Section: Introductionmentioning
confidence: 96%
“…Consistent with this hypothesis, Cusson et al recently reported the formation of a nine‐membered lactone by RCM reaction which was highly dependent on the configuration of one of three of the stereocentres in the substrate . Other examples of diastereoselective RCM reactions have been reported for five‐ and six‐membered ring formations , . Interestingly, there appear to be subtle differences between the tri‐TBDPS‐protected and tri‐TBDMS‐protected substrates that allows medium ring formation of both epimers for the former, possibly simply due to increased protecting group size.…”
Section: Resultsmentioning
confidence: 99%
“…[24] Other examples of diastereoselective RCM reactions have been reported for fiveand six-membered ring formations. [25,26] Interestingly, there appear to be subtle differences between the tri-TBDPS-protected and tri-TBDMS-protected substrates that allows medium ring formation of both epimers for the former, possibly simply due to increased protecting group size.…”
Section: Oxidationmentioning
confidence: 99%
“…Substances are separated with liquid chromatography using different solvent mixtures with silica gel [13], charcoal [17] and sephadex [14] [18]. Other types of analytical techniques include thin layer chromatography (TLC) and high performance liquid chromatography (HPLC) [19]- [22].…”
Section: Chemical Constituentsmentioning
confidence: 99%